The relationship between positive thinking, social support, and students’ psychological well-being during online learning - Haris Munandar; Herman Herman; Dimas Adi Putra; Nilam Nilam (Program Studi bimbingan Konseling PPs UNM Makassar, 2022)
This research aimed to see the relationship between positive thinking and social support with psychological well-being in UMPR PGSD students during online learning. The research was conducted in Muhammadiyah University of Palangkaraya campus area. The subjects were UMPR PGSD students who had taken the 4th semester of college minimal or above in this research. The sampling technique used purposive sampling with criteria. This research used quantitative method by correlational study approach. Data analysis method used correlational analysis technique or regression analysis in this research. This research result was found that there were significant relationship between positive thinking and social support with psychological well-being in UMPR PGSD students during online learning with correlation coefficient (R) of 0.707 which was converted to F Regression of 28.407 with significance level of 0.000 (p< 0.05). The conclusion of the research was that the higher positive thinking and social support obtained students, the higher psychological well-being on students will be followed, n the other hand, the lower the high of positive thinking and social support obtained students, the lower the psychological well-being on students will be followed.